Variance analysis and linear contracts in agencies with distorted performance measures - Jörg Budde (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
This paper investigates the role of variance analysis procedures in aligning objectives under the condition of distorted performance measurement. A riskneutral agency with linear contracts is analyzed, whereby the agent receives postcontract, pre-decision information on his productivity. If the performance measure is informative with respect to the agent's marginal product concerning the principal's objective, variance investigation can alleviate effort misallocation. These results carry over to a participative budgeting situation, but in this case the variance investigation procedures are less demanding.
urn:nbn:de:bvb:19-epub-13346-1
Keywords: 330